Edukasi Usia Dini: School Based Vector Control (SBVC) dengan menggunakan Media Daur Ulang Sekam Padi di TK Mawar Kecamatan Gambut - Norsita Agustina; Chandra Chandra; Edy Ariyanto; Muhammad Febriza Aquarista (Universitas Mathla'ul Anwar Banten, 2021)
AN EARLY AGE EDUCATION: SCHOOL BASED VECTOR CONTROL (SBVC) USING RICE HUSK RECYCLING MEDIA IN MAWAR KINDERGARTEN, GAMBUT DISTRICT. In realizing vector-free healthy schools it needs to be improved, because of the increasing number of infectious diseases caused by vectors such as DHF, diarrhea, scabies, and typhoid, in students. Steps that can be taken to build a Clean and Healthy Life Behavior (PHBS) in preventing and controlling the proliferation of disease vectors is one of them with the introduction of School Based Vector Control (SBVC) in schools through the media of sticking husks on paper patterned animals that spread disease. The purpose of this research is the establishment of the SBVC model and the effectiveness of the SBVC model as an effort to increase knowledge of the introduction of diseases caused by animals spreading disease through mosaic techniques using rice husks and Madihin art performances for the preservation of the art of Banjar, South Kalimantan. This community service was conducted in Mawar Kindergarten, Gambut District with 50 students and 5 homeroom teachers from TK B. The conclusion from the implementation of community service is students and homeroom teachers know animals that spread the disease and can utilize rice husk waste as a learning media based on Ecogreen and can preserve Banjar art, namely “Madihin”.